ANALYSIS OF DYNAMICS OF ANTIBIOTIC RESISTANCE OF PATHOGENS IN PATIENTS WITH DIABETIC FOOT SYNDROME UNDERGOING IN-PATIENT TREATMENT - Galina Batishcheva; Tatyana Malorodova; Tatyana Pokrovskaya; Elena Kazakova; Zhanna Urozhevskaya; Nina I. Zhernakova; Ol'ga Osipova (Belgorod National Research University, 2016)
Persistent ulcers in patients with diabetic foot syndrome in 85% of cases lead to amputation because of secondary infection and growing gangrene that significantly worsen the prognosis. In the course of our study, the data were obtained on the role of the staphylococcus, Pseudomonas aeruginosa infections, Enterobacteriaceae isolates, and, in a small percentage of cases, Candida fungus in diabetic foot syndrome. It was shown that in case of incomplete eradication of the pathogen the structure of pathogens and its sensitivity to antibiotics undergo changes. In this case, methicillin-resistant staphylococci and Pseudomonas aeruginosa are detected. In this paper we discuss the approaches to the choice of antibiotic therapy, subject to the sensitivity of these microorganisms to antibiotic therapy in the surgical department of St. Joseph Belgorod Regional Clinical Hospital. The obtained data state that III-IV generation pseudomonas cephalosporins and fluoroquinolones can be used for empirical therapy. And, in case of staphylococcal infections, - vancomycin.